2020
DOI: 10.21203/rs.2.20313/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Household Food Insecurity, Coping Strategies and Adolescent Girls’ Dietary Diversity Status in Hossana Town, Ethiopia.

Abstract: Background: Adolescents (10-19 years) represent 20 % of the world’s population. In Ethiopia they account for 20-26% of the general population. With adequate dietary diversity, this period is a window of opportunity to break intergenerational cycle of malnutrition. However, there is scarcity of data on the status of dietary diversity in this segments of the population. Methods: A community based cross sectional study design was employed from May 21-June 20, 2019. Cluster sampling technique was used to collect d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…However, it was higher than the ndings of studies conducted in India(6), Nigeria`s Ibadan metropolis (29), Ethiopia, Hosanna town (9), and Woliata Sodo town (23). This high prevalence might be attributed to the current high food price in ation, implications of security problems in different parts of the country, and the war in northern parts which hinders farming activity.…”
Section: Factors Associated With Household Food Insecurity In Multiva...mentioning
confidence: 61%
See 1 more Smart Citation
“…However, it was higher than the ndings of studies conducted in India(6), Nigeria`s Ibadan metropolis (29), Ethiopia, Hosanna town (9), and Woliata Sodo town (23). This high prevalence might be attributed to the current high food price in ation, implications of security problems in different parts of the country, and the war in northern parts which hinders farming activity.…”
Section: Factors Associated With Household Food Insecurity In Multiva...mentioning
confidence: 61%
“…In 2015, a National level longitudinal study revealed that nearly 1 in 5(18.6%) of smalltown households and 1 in 7 (13.6%) of large-town households were uncertain about having food for the family all over the year(8). And the other study in Hosanna town revealed that 41.7% of households or 2 in 3 were food insecure (9).…”
mentioning
confidence: 93%
“…As adolescents go about their day-to-day business in environments where they live, study and play, food insecurity remains a challenge they continually face (Sholeye et al, 2021). Adolescence is a critical period of life characterized by: rapid physical and psychological growth spurts; development of intellectual cognition and psychological capacity; and a chance to interrupt the cycle of trans-generational malnutrition and other nutritional problems (Bancha et al, 2020;Dewi et al, 2020). Food insecurity among adolescents has been documented to be associated with: malnutrition, poor health outcomes, low educational attainment, bullying, somatic symptoms such as headaches, tiredness and malaise, mental health problems including stress and suicidal ideations, sexual risk-taking, transactional sex and increased HIV prevalence (Wolde et al, 2015;Drammeh et al, 2019;Dewi et al, 2020;Seidu et al, 2020;Onono et al, 2021).…”
Section: Introductionmentioning
confidence: 99%